Robust speed synchronization control for clutchless automated manual transmission systems in electric vehicles. (March 2015) - Zhu, Xiaoyuan; Zhang, Hui; Xi, Junqiang; Wang, Junmin; Fang, Zongde
This paper is concerned with the speed synchronization optimal controller design problem for clutchless automated manual transmission systems in electric vehicles. It is well known that speed synchronization is one of the main challenges in a transmission system. In electric vehicles, clutchless automated manual transmission systems are regarded as promising transmission devices and are generally required to have high-precision speed synchronization capabilities. In order to satisfy this requirement, a robust optimal speed synchronization control scheme is proposed in this paper. The control law consists of preview control, integral control, and state-feedback control. Using an augmentation method, the proposed controller design problem is transformed into a state-feedback design problem for the augmented system first. As the external input is involved in the augmented system, the H ∞ control scheme is employed to minimize the effect of disturbance on the controlled output. In addition, to ensure tradeoff between the transient response and the maximal control effort, the linear quadratic cost function and the pole placement technique are also adopted in the design. Finally, the controller gains are calculated by solving the linear matrix inequality. Simulation results show the effectiveness of the proposed control approach.